Warning sign as a predictor of dengue infection severity in children (Faculty of Medicine Universitas Indonesia, 2018)
Background: Dengue has emerged as a global public health problem, about 500,000 affected patients of 50â100 million cases will develop severe dengue infection. Therefore, early identification of severe dengue infection symptoms can save a patientâs life. The 2009 WHO dengue infection classification proposed seven warning signs to identify the risk of severe dengue. This study was conducted to predict the severity of dengue infection based on the number of warning signs. Methods: This was a diagnostic study conducted with a retrospective analytic observation of patients admitted to Adam Malik hospital with a diagnosis of dengue infection from January 2014-May 2016. The association between warning signs and severe dengue infection was analyzed using logistic regression. We also analyzed the sensitivity, specificity, positive predictive value and negative predictive value. Results: Of 140 patients who fulfilled the research criteria were collected from the medical records. The patients were classified as severe dengue (n=28) and nonsevere dengue (n =112). The warning signs that were associated with severe dengue were persistent vomiting (p<0.05, OR 31.9, 95%CI), fluid accumulation (p<0.05, OR 22.4, 95%CI), mucosal bleeding (p<0.05, OR 9.1, 95%CI), lethargy (p<0.05, OR 43.1, 95%CI). After analyzing the diagnostic tests, the combination of three or more warning signs showed that sensitivity of 92.9%, specificity of 78.6%, positive predictive value of 52%, negative predictive value of 97.7% was found to be associated with a severe dengue infection. Conclusion: The combination of three or more warning signs showed a high sensitivity and specificity for predicting a severe dengue infection.